Nonlinear Dynamics of Buck Converter (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper is concerned with the problem of modeling and simulation of piecewise linear systems with the pulse width modulation control. Models of this kind of systems are widely used in engineering practice, in particular in power electronic converters. The research provides the study of chaos and bifurcations in one of the switching converters – step-down converter under voltage mode control, operating in discontinuous and continuous current modes, using Matlab and Simulink simulation environment. Various types of models, including discrete – time maps, switched state – space models are examined in order to detect their suitability and reliability in numerical investigation of nonlinear phenomena in DC–DC converters. Some analytical methods for the search of periodic regimes and their stability estimation were also used in order to validate numerically obtained results and evaluate the accuracy of models used. As direct simulation does not accurately pinpoint bifurcation points and computes only stable invariant sets, some aspects and advantages of numerical path-following are also discussed.